Chronic Kidney Disease Induced Intestinal Mucosal Barrier Damage Associated with Intestinal Oxidative Stress Injury. (14th July 2016) - Yu, Chao; Wang, Zhen; Tan, Shanjun; Wang, Qiang; Zhou, Chunyu; Kang, Xin; Zhao, Shuang; Liu, Shuai; Fu, Huijun; Yu, Zhen; Peng, Ai
Abstract : Background. To investigate whether intestinal mucosal barrier was damaged or not in chronic kidney disease progression and the status of oxidative stress. Methods. Rats were randomized into two groups: a control group and a uremia group. The uremia rat model was induced by 5/6 kidney resection. In postoperative weeks (POW) 4, 6, 8, and 10, eight rats were randomly selected from each group to prepare samples for assessing systemic inflammation, intestinal mucosal barrier changes, and the status of intestinal oxidative stress. Results. The uremia group presented an increase trend over time in the serum tumor necrosis factor-alpha, interleukin-6 (IL-6) and IL-10, serum D-lactate and diamine oxidase, and intestinal permeability, and these biomarkers were significantly higher than those in control group in POW 8 and/or 10. Chiu's scores in uremia group were also increased over time, especially in POW 8 and 10. Furthermore, the intestinal malondialdehyde, superoxide dismutase, and glutathione peroxidase levels were significantly higher in uremia group when compared with those in control group in POW 8 and/or 10. Conclusions. The advanced chronic kidney disease could induce intestinal mucosal barrier damage and further lead to systemic inflammation. The underlying mechanism may be associated with the intestinal oxidative stress injury.